2021
DOI: 10.1002/pros.24224
|View full text |Cite
|
Sign up to set email alerts
|

Increased risk of postoperative in‐hospital complications after radical prostatectomy in patients with prior organ transplant

Abstract: Background:To analyze postoperative, in-hospital, complication rates in patients with organ transplantation before radical prostatectomy (RP).Methods: From National Inpatient Sample (NIS) database (2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015) prostate cancer patients treated with RP were abstracted and stratified according to prior organ transplant versus nontransplant. Multivariable logistic regression models predicted in-hospital complications.Results: Of al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Smoking has now become one of the main risk factors threatening the incidence of Chinese population and it is the main cause of cardiovascular disease, cancer and other diseases and the death of patients with various diseases. The number of smokers in my country accounts for 30 % of the total number of smokers in the world, which makes the disease burden caused by smoking very serious; a survey study found that smoking ranks second among 87 causes of death, second only to high blood pressure [17] . Smoking was a risk factor for postoperative recurrence and metastasis.…”
mentioning
confidence: 99%
“…Smoking has now become one of the main risk factors threatening the incidence of Chinese population and it is the main cause of cardiovascular disease, cancer and other diseases and the death of patients with various diseases. The number of smokers in my country accounts for 30 % of the total number of smokers in the world, which makes the disease burden caused by smoking very serious; a survey study found that smoking ranks second among 87 causes of death, second only to high blood pressure [17] . Smoking was a risk factor for postoperative recurrence and metastasis.…”
mentioning
confidence: 99%